(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: To examine the effect of a Leptadenia reticulata leaf extracts on glucose concentrations and lipid profiles in rats with and without diabetic. Material and methods: Streptozotocin caused diabetes in Wistar rats. Oral administration of Leptadenia reticulata leaf extracts in petroleum ether, ethyl acetate, and ethanol at a rate of 200 mg/kg was performed. Metformin (50 mg/kg), a common diabetes medication, was evaluated for its ability to reduce glucose levels and hypolipidemia. Results: According to the findings of the sub-acute toxicity investigation, there was no discernible change in animal behaviour as a result of the lack of toxicity. In diabetic rats, the ethanol extract effectively diminished glucose levels (P<0.05), as well as cholesterol and triglyceride levels, and increased HDL levels. conclusion: In conclusion, the current study provides scientific support for the traditional usage of Leptadenia reticulata in the treatment of diabetes and cardiovascular disease. Moreover, the ethanol extract of Leptadenia reticulata (ETLR) are found to be more active against hyperglycaemia and hyperlipidaemia.